Students' Perception towards Online Teaching Learning Activities During COVID-19 - Upadhayaya, Parshu Ram (Ganeshman Darpan, 2022)
Educational institutes across the world have closed due to the COVID-19 pandemic. Most educational institutes have shifted to online learning platforms. In this background, study aim was to find out the perception of students towards online-class during COVID-19 pandemic. The study was carried out by using the structured questionnaire survey, and self-administered online Google form was developed to collect the data. The data were collected from 199 students of public college. The reliability test of collected data was checked by calculating the Cronbach’s Alpha value. Frequency, percentage, and mean was used to analyze the data. Finding of the study revealed that 77.4% students adopted online class in their learning by using mobile devices. However, majority of respondents felt confident to use online-class function and adopt content. Similarly, 71.9% respondents reported that they used the mobile phone data (for internet) during online-class, majority of respondents believed that online class was one of the easiest platforms to share the knowledge and collect the required information. The analysis showed that the common online platforms in Nepal were Zoom, Microsoft Teams offering online interactive classes. They also agreed on the advantages of online learning. Majority of the students preferred to use smart phone for online learning. The benefits were mainly self-learning, low costs, convenience, and flexibility.